Blood Pressure, Total Cholesterol, and Triglycerides Associated with Cardiovascular Risk Score in Low 25-Hydroxy Vitamin D Level among Online Motorcycle Drivers, Jakarta, Indonesia - Kalumpiu, Joice Viladelvia; Herwana, Elly; Yenny, Yenny; Kurniasari, Kurniasari (Global Medical & Health Communication (GMHC), 2024)
Low 25-hydroxy vitamin D is associated with many chronic diseases, such as coronary heart disease. Online motorcycle drivers spend prolonged hours on the road and may face many stressors and occupational hazards that can create the development of cardiovascular disease. This study aims to determine factors contributing to cardiovascular risk among online motorcycle drivers. This study was an observational analytic with a cross-sectional design. Data were collected in September 2022  with consecutive random sampling methods for 114 subjects at Universitas Trisakti Jakarta. The ages of the subjects ranged from 25 to 62 years. Cardiovascular risk was assessed based on the Jakarta Cardiovascular Risk Score (JAKVAS). The data collection included physical examination and blood biochemistry (lipid profile, fasting blood glucose, and 25(OH)D). The data were analyzed using a chi-square test with p<0.05. The majority of subjects were male 83 (72.8%). On blood pressure examination, mean systolic blood pressure was 128.9±16.7 mmHg, and diastolic blood pressure was 86.7±11.9 mmHg. The mean cardiovascular risk was 4.4±2.8, and 52.6% had a high-risk score. All subjects had low 25(OH)D serum levels, with mean 25(OH)D serum levels of 18±5.7 ranging between 6.9 and 29.8. Among online motorcycle drivers, there was a significant association between blood pressure, total cholesterol, and triglyceride with cardiovascular risk scores in low 25-hydroxy vitamin D levels. Blood pressure, total cholesterol, and triglyceride could affect cardiovascular health in low 25-hydroxy vitamin D levels among online motorcycle drivers.